The Implicature of Language Style in Alice in Wonderland Movie - Cahyani Fitri Melania; Ansor Putra; Neil Amstrong (ELITE: Journal of English Language and Literature, 2017)
Language style and implicature meaning are two important aspects that are related in conversation, especially the conversation in Alice in Wonderland movie. In this research, the researcher found the characters’ utterances that contain language style and the relation to the implicature meaning behind their utterances. This research aims to analyze the type of language style used by the characters in Alice in Wonderland movie based on the Joos’ theory of language style (1967) and the relation between language style and the implicature meaning behind the character’s utterance in Alice in Wonderland movie based on the Yule theory of implicature (1996). The researcher used a qualitative descriptive method in this research. In this research, all of the characters in Alice in Wonderland movie are using the five types of language style which is frozen style, formal style, consultative style, casual style, and intimate style. The researcher also found that there is a relation between the language style that used by the characters in Alice in Wonderland and the implicature meaning in behind the characters’ utterances. By using the language style, Alice can use the proper language when talking to her interlocutor and also, by understanding the implicature meaning, Alice can understand the meaning behind their utterance so there is no misunderstanding between them.